Single shaft GT D045 mathematical model - Чобенко, Владимир Николаевич; Палиенко, Роман Васильевич; Лютиков, Александр Леонидович (Eastern-European Journal of Enterprise Technologies, 2013)
The design and development processes of GTE are based on wide use of mathematical models reflecting the physical picture of the engine functioning. The method of modeling processes in a gas turbine engine with detailed calculation of the turbine tract to the blading level is described in this article. Principles of construction and structure of the single-shaft gas turbine engine for power industry mathematical model is recounted. The modeling features of both the single shaft GTE in general and the D045 engine in particular are also described. The model allows to take it possible to solve different tasks which are related to the calculation of the GTE static performances in a wide range of external conditions and operation modes, arising in the design and development process of the gas turbine engine. The created mathematical model will be identified according to the results of the bench tests in order to its further usage in the development work